A Note on the Equivalence Between Observed and Expected Information Functions With Polytomous IRT Models. (February 2015) - Magis, David
The purpose of this note is to study the equivalence of observed and expected (Fisher) information functions with polytomous item response theory (IRT) models. It is established that observed and expected information functions are equivalent for the class of divide-by-total models (including partial credit, generalized partial credit, rating scale, and nominal response models) but not for the class of difference models (including the graded response and modified graded response models). Yet, observed information function remains positive in both classes. Straightforward connections with dichotomous IRT models and further implications are outlined.